2022
DOI: 10.1186/s12889-022-12750-8
|View full text |Cite
|
Sign up to set email alerts
|

Physical environmental opportunities for active play and physical activity level in preschoolers: a multicriteria analysis

Abstract: Background Active play opportunities seems to influence the level of physical activity during childhood. However, a gap remains about which environmental opportunities including the daycare physical environment could have a positive impact on the level of physical activity in preschoolers. Objectives (1) To develop an index to measure the environmental opportunities of free active play for preschoolers of middle-income countries; (2) to check the r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 79 publications
1
4
0
Order By: Relevance
“…This environment may positively or negatively influence children’s physical activity levels and health (Herr et al, 2021 ; Hodges et al, 2013 ; Cosco et al, 2010 ; Timmons et al, 2012 ). The examined schools had an average quality score of 2.6 ± 0.16 points, which corresponds to a space considered inadequate, corroborating other Brazilian studies (NOBRE et al, 2022 ). However, it is noteworthy that small improvements in school quality appear to benefit the development of children (Morais et al, 2021 ).“ For example, Trost et al, 2010 , argue that the larger the space of schools, the greater the possibility of children’s physical activity engagement; consequently, they have more probability of developing MC.…”
Section: Discussionsupporting
confidence: 87%
“…This environment may positively or negatively influence children’s physical activity levels and health (Herr et al, 2021 ; Hodges et al, 2013 ; Cosco et al, 2010 ; Timmons et al, 2012 ). The examined schools had an average quality score of 2.6 ± 0.16 points, which corresponds to a space considered inadequate, corroborating other Brazilian studies (NOBRE et al, 2022 ). However, it is noteworthy that small improvements in school quality appear to benefit the development of children (Morais et al, 2021 ).“ For example, Trost et al, 2010 , argue that the larger the space of schools, the greater the possibility of children’s physical activity engagement; consequently, they have more probability of developing MC.…”
Section: Discussionsupporting
confidence: 87%
“…In general, elementary schools in very high and high HDI countries/localities have structures and opportunities for organized sports and PA, which are not observed for children in low-income countries. 14 We found that children and adolescents living in urban areas of the countries/localities with low/medium HDI achieved better grades than those living in urban areas of the countries/localities with very high and high HDI for the Active transportation indicator. However, when analyzing only children and adolescents living in rural areas, the results were the opposite, in which those from very high HDI countries had higher grades than those from lower HDI countries for the Organized sport and PA and Active play indicators.…”
Section: Discussionmentioning
confidence: 64%
“…The free time available to children is largely allocated to SBs, and PA diminishes with age [3,34]. Following this logic, the preschoolers analyzed during the COVID-19 period remained within this same scenario, with certain additional particularities, characterized by a positive impact on PA when parents were more available or subjected to less stress when dealing with their children, a greater number of children in the area, and freedom to play outside the home [3,21,27,31,35].…”
Section: Discussionmentioning
confidence: 99%
“…Although the excessive employment of Information and Communication Technologies (ICTs) by children has been a prevailing issue [26], the imposition of lockdown measures has accentuated its impact on both children and adults, given the widespread use of computers and near-universal access to the internet. The ramifications of this excessive screen usage have necessitated the proposal of preventive programs and the development of tools to identify addiction and other behavioral issues [27]. To ameliorate this situation, it has been established that a balanced amalgamation of lifestyle behaviors during childhood, encompassing reduced ST, the adoption of healthy dietary patterns, and regular PA, is necessary [28].…”
Section: Discussionmentioning
confidence: 99%